Proactive analysis of road traffic accidents in the Republic of Kazakhstan based on machine learning models and geographic information systems - Kobdikova, Sh.; Chupekov, Y.; Arimbekova, P.; Nokhatov, M.; Кобдикова, Ш. М.; Чупеков, Ю. К.; Аримбекова, П. М.; Нохатов, M. А. (Харківський національний автомобільно-дорожній університет, 2025)
The article is devoted to the development of a methodology for proactive analysis of road traffic accidents (RTAs) in the Republic of Kazakhstan (RK). Traditional retrospective approaches do not provide sufficient effectiveness in preventing incidents under conditions of annually. increasing acci-dent rates and significant socio-economic losses, which exceed USD 7 billion per year. Goal. The aim of this study is to provide a theoretical justification for a proactive analysis methodology based on machine learning (ML) models. Methodology. The proposed approach is grounded in the integration of Big Data obtained from the national digital platform TOR (Traffic Operational Response) and the application of predictive ML models such as Random Forest and XGBoost. Originality. The scientific novelty lies in the synthesis of ML models and GIS-based analysis to create a dynamic proactive model for RTA risk assess-ment, adapted for the first time to the specific data environment of Kazakhstan. The developed framework enables the prediction of both the probability and the severity of RTAs on specific road segments using dy-namic influencing factors. Results.The results can be utilized by road infrastructure agencies and law en-forcement bodies in Kazakhstan for targeted patrolling and proactive interventions. Practical value. It is recommended to integrate the ML module directly into the TOR platform and to establish standardized interagency data exchange procedures.
Проактивний аналіз дорожньо-транспортних пригод у Республіці Казахстан на основі моделей машинного навчання та геоінформаційних систем
Keywords: proactive rta analysis; machine learning; random forest; xgboost; gis analysis; big data; TOR (Traffic Operational Response); risk prediction; Kazakhstan; road safety; проактивний аналіз RTA; ма-шинне навчання; випадковий ліс; гіс-аналіз; великі дані; TOR (реагування на дорож-ній рух); прогнозування ризиків; Казахстан; безпека дорожнього руху; 656.13; 10.30977/AT.2219-8342.2025.57.0.07